Problems of selection criteria and genetic evaluations of the goat population in the north of Morocco - Analla M.; Serradilla J.M. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
The goat population in northern Morocco is very heterogeneous, with influence of some Spanish as well as French breeds. The preliminary economic studies suggest that goat breeding should be oriented towards milk production for cheese making. Thus, selection criteria should be chosen according to this objective. Concerning the genetic evaluation procedure, the possibility to include the longevity as a measure of their adaptation and overall resistance to diseases, should be considered. Moreover, non additive genetic effects, likely to be very important due to heterogeneity of the goat population, should be accounted for during routine genetic evaluations.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)